Assessment of mutual influence of factors on crane emergency - Sladkova L.A.; Krylov V.V.; Neklyudov A.N. (Naučno-Tehničeskij Vestnik Brânskogo Gosudarstvennogo Universiteta, 2020)
Existing methods of assessing the influence of factors allow to determine this influence indirectly without taking into account the speed (intensity) of their influence and the relationship between them. The article proposes a method of assessing the complex impact of significant factors on the failures of cranes, the relationship between which is presented in the form of a kinetic system, changing over time depending on the change of any active factor. The accumulated statistical material of accidents on cranes of different kinds are the initial data in the conduct of studies to assess the cumulative effect of various factors on the performance of crane equipment. The proposed methodology will take into account the intensity of the changes in factors associated with their change. This takes into account the kinematic state of the current factors, which is determined by the speed of change of each external factor, depending on the related factors acting on it. The results of the evaluation of crane failures under the proposed methodology do not contradict the studies of other authors and allow to assess the intensity of mutual influence of factors on each other.